PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA KONVEKSI BAPAK JUKARI DI KAMPUNG INDUSTRI KECIL CEGER JURANG MANGU TIMUR KOTA TANGERANG SELATAN - Abdul Karim Abdul Karim; Ade Rachmawan (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to analyze and explore the operational dynamics of Mr. Jukari’s home-based garment industry in Kampung Industri Kecil Ceger, Jurang Mangu Timur, South Tangerang. Specifically, this research focuses on three primary objectives: (1) identifying obstacles in improving product quality, (2) examining the promotional strategies implemented to enhance customer satisfaction, and (3) empirically testing the influence of product quality and promotion on customer satisfaction levels.The analytical method employed in this study is simple linear regression analysis to test the influence between variables. The data analysis techniques used are Descriptive and Inferential Statistics, with a sample size of 100 customers. The results indicate that product quality (X1) has a positive influence on customer satisfaction (Y) with the regression equation Y = 5.944 + 0.385. This suggests that any improvement in product quality will be followed by a significant increase in customer satisfaction. Consistently, the promotion variable (X2) also demonstrates a strong positive influence on customer satisfaction (Y) with the regression equation Y = 5.954 + 0.931. These findings confirm that effective promotional strategies are a crucial factor in driving consumer satisfaction within this garment business unit. Based on the findings, it is recommended that home-based industry owners minimize production obstacles to maintain quality consistency and optimize promotional channels for business sustainability amidst small-scale industrial competition. Keywords: Product Quality, Promotion, Customer Satisfaction, Small Industry, Garment.